Evaluasi Sifat Fisik Sediaan Sabun Cair Ekstrak Bunga Telang (Clitoria ternate) - Kusumawati, Dwi Endah; Puspitasari, Rega (Sultan Agung Islamic University of Semarang, 2023)
Background: Antiseptic liquid soap is increasingly popular with the public. The antibacterial substance that is usually contained in antiseptic liquid soap is triclosan, which when used in the long term can disrupt the balance of the normal flora on the skin, so natural ingredients are needed to replace the use of triclosan. One of the natural ingredients that can be used is butterfly pea. The aim of the study was to evaluate the physical properties of the butterfly pea liquid soap (organoleptic, pH, specific gravity, viscosity and foam stability) in accordance with the requirements listed in the SNI for liquid soap. Methods: This study is an analytical experiment, namely testing and analyzing the characteristics of butterfly pea liquid soap which consists of: organoleptic (consistency, color, aroma), pH, viscosity, and foam stability. Results: Hand washing liquid soap with butterfly pea flower extract complies with SNI requirements, with details: purple in color with slightly thick consistency, pH 4.5 – 5 , specific gravity 1.02 – 1.03 g/mL, viscosity 3456.33 – 6375.33 cP with foam stability of 93%. Conclusion: The physical characteristics of liquid hand washing soap with the active ingredient of butterfly pea flower extract comply with the requirements of SNI and have a purple color due to the presence of anthocyanin.